Collaborative Governance for the Construction of Public Policies on Social Sustainability - Callegaro, Sabrina (Conference on Digital Government Research, 2025)
Government actors promoting collaborative initiatives for a more inclusive and democratic society must understand that effective strategies for lasting social impact demand significant effort. Collaborative governance relies on the interaction between the government, private sector, and civil society. However, success is not guaranteed by collaboration alone, due to various factors can affect decision-making effectiveness. This article explores the key factors in collaborative governance, with a specific focus on social sustainability, to optimize governance practices. The field research was conducted using a qualitative approach through a case study in Porto Alegre city, Brazil. We conducted semi-structured interviews with 16 stakeholders, analysed documents, and performed direct observations. The study provides valuable insights for public managers and governments on effective strategies for addressing social issues and improving governance, aiming to enhance social sustainability and project efficiency. Additionally, it identifies factors for collaborative governance in the Latin America context.